Science popularization on Facebook: statistical analysis of posts from a Brazilian university (Intercom - Brazilian Journal of Communication Sciences, 2023)
This study performed a statistical analysis of the repercussions of a project concerning science popularization (SP) during the first 14 months of execution in a Brazilian public university. The metrics used were the results achieved from posts of 95 videos disseminating scientific research on the institution’s Facebook page. The objective was to verify the dialogical potential of the project while considering that social media increase the possibilities for public participation. Analyses included general descriptive data (means, minima, maxima, and standard deviations), Pearson’s correlation coefficients, and clusters’ formation. Among the main results, we verified that the published videos can be divided into five clusters, which differ by the level of interaction/reach. The research themes, text, and video strategies used in the posts modulate the potential for interaction with the public. The results are helpful for the future planning of SP actions.
Keywords: Science popularization; Facebook; Public mobilization; Public university; Scientific research